Establishment of infection prevention and control strategy in nursing managements during surgical operations in COVID‐19 patients based on Delphi method - Qi Wu; Hui‐juan Jiang; Han‐qian Chen (Wiley, 2023)
Abstract Aim The aim of this study was to establish an infection prevention and control strategy for nursing managements during surgical operations in coronavirus disease 2019 (COVID‐19) patients. Design A Delphi method. Methods Between November 2021 and March 2022, we first formulated a preliminary infection prevention and control strategy based on the literature review and institutional experience. Then, we applied Delphi method and performed expert surveys to reach a final strategy for nursing managements during surgical operations in COVID‐19 patients. Results The strategy included seven dimensions with 34 items. The positive coefficients of Delphi experts in both surveys were 100%, indicating a high coordination among experts. The degree of authority and expert coordination coefficient were 0.91 and 0.097-0.213. After the second expert survey, value assignments for importance of each dimension and item were 4.21-5.00 and 4.21-4.76 points, respectively. The coefficients of variation for dimension and item were 0.09-0.19 and 0.05-0.19, respectively. Patient or Public Contribution Except the medical experts and research personnel, there was no other patient or public contribution involved in the study.